Arabidopsis FNRL protein is an NADPH‐dependent chloroplast oxidoreductase resembling bacterial ferredoxin‐NADP+ reductases. Issue 2 (12th November 2017) - Koskela, Minna M.; Dahlström, Käthe M.; Goñi, Guillermina; Lehtimäki, Nina; Nurmi, Markus; Velazquez‐Campoy, Adrian; Hanke, Guy; Bölter, Bettina; Salminen, Tiina A.; Medina, Milagros; Mulo, Paula
Abstract : Plastidic ferredoxin‐NADP + oxidoreductases (FNRs; EC:1.18.1.2) together with bacterial type FNRs (FPRs) form the plant‐type FNR family. Members of this group contain a two‐domain scaffold that forms the basis of an extended superfamily of flavin adenine dinucleotide (FAD) dependent oxidoreductases. In this study, we show that the Arabidopsis thaliana At1g15140 [Ferredoxin‐NADP + oxidoreductase‐like (FNRL)] is an FAD‐containing NADPH dependent oxidoreductase present in the chloroplast stroma. Determination of the kinetic parameters using the DCPIP NADPH‐dependent diaphorase assay revealed that the reaction catalysed by a recombinant FNRL protein followed a saturation Michaelis–Menten profile on the NADPH concentration with k cat  = 3.2 ± 0.2 s −1, K m NADPH  = 1.6 ± 0.3 μ M and k cat / K m NADPH  = 2.0 ± 0.4 μ M −1  s −1 . Biochemical assays suggested that FNRL is not likely to interact with Arabidopsis ferredoxin 1, which is supported by the sequence analysis implying that the known Fd‐binding residues in plastidic FNRs differ from those of FNRL. In addition, based on structural modelling FNRL has an FAD‐binding N‐terminal domain built from a six‐stranded β‐sheet and one α‐helix, and a C‐terminal NADP + ‐binding α/β domain with a five‐stranded β‐sheet with a pair of α‐helices on each side. The FAD‐binding site is highly hydrophobic and predicted to bind FAD in a bent conformation typically seen in bacterial FPRs.